Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2024
DOI: 10.1002/ardp.202400011
|View full text |Cite
|
Sign up to set email alerts
|

GOAT rs10096097 and CREB1 rs6740584 single nucleotide polymorphisms are associated with type 2 diabetes mellitus in Egyptians

Nancy N. Shahin,
Olfat G. Shaker,
Mohamed O. Mahmoud

Abstract: Diabetes mellitus (DM) is a chronic disorder that affects nearly half a billion people around the world and causes millions of deaths annually. Treatment of diabetes or related complications represents an economic burden not only for developing countries but also for the developed ones. Hence, new efficient therapeutic and preventive strategies and screening tools are necessary. The current work aimed to assess the potential association of single nucleotide polymorphisms (SNPs) in ghrelin O‐acyltransferase (GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“…Previous studies have reported that EPAS1 [486], HOXA1 [735], TGM2 [449], CCND2 [500], EGFR (epidermal growth factor receptor) [276], NEDD4L [496], DCLK1 [504], hsa-mir-363-3p [738], hsa-mir-21-5p [743], SMAD4 [744], ATF3 [745], TBX5 [746], SREBF1 [747], SMARCA4 [748] and CREB1 [749] were regulated in cardiovascular diseases. Studies reported that ERBB3 [255], TGM2 [223], CCND2 [274], EGFR (epidermal growth factor receptor) [276], hsa-mir-21-5p [750], ATF3 [751], SREBF1 [752], ARNT (aryl hydrocarbon receptor nuclear translocator) [753] and CREB1 [754] play important roles in diabetes mellitus. ERBB3 [340], TGM2 [319], EGFR (epidermal growth factor receptor) [367], DCLK1 [366], SMAD4 [755], SREBF1 [756] and CREB1 [757] participated in the regulation of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that EPAS1 [486], HOXA1 [735], TGM2 [449], CCND2 [500], EGFR (epidermal growth factor receptor) [276], NEDD4L [496], DCLK1 [504], hsa-mir-363-3p [738], hsa-mir-21-5p [743], SMAD4 [744], ATF3 [745], TBX5 [746], SREBF1 [747], SMARCA4 [748] and CREB1 [749] were regulated in cardiovascular diseases. Studies reported that ERBB3 [255], TGM2 [223], CCND2 [274], EGFR (epidermal growth factor receptor) [276], hsa-mir-21-5p [750], ATF3 [751], SREBF1 [752], ARNT (aryl hydrocarbon receptor nuclear translocator) [753] and CREB1 [754] play important roles in diabetes mellitus. ERBB3 [340], TGM2 [319], EGFR (epidermal growth factor receptor) [367], DCLK1 [366], SMAD4 [755], SREBF1 [756] and CREB1 [757] participated in the regulation of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%